Dead head redemption ebook - Various, Marvel (Deadpool (2008), 2024)
Collects Deadpool #900 and Deadpool #1000. Thrill as the Merc with a Mouth squares off against probe-happy aliens, trigger-happy mimes, mimes from outer space, urban cannibals, underage hit men, one seriously unhappy fanman and Lady Luck herself!